2021
DOI: 10.37201/req/049.2021
|View full text |Cite
|
Sign up to set email alerts
|

Current microbiological aspects of community respiratory infection beyond COVID-19

Rafael Cantón

Abstract: From a microbiological point of view, both empirical and targeted antimicrobial treatment in respiratory infection is based on the sensitivity profile of isolated microorganisms and the possible resistance mechanisms that they may present. The latter may vary in different geographic areas according to prescription profiles and vaccination programs. Beta-lactam antibiotics, fluoroquinolones, and macrolides are the most commonly used antimicrobials during the exacerbations of chronic obstructive pulmonary diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
2
0
4
Order By: Relevance
“…Spanish authors have suggested that, besides year-to-year variability, the increase in bacterial and viral isolations over time might reflect a changing epidemiology due to a potential increase in patients with worse socio-sanitary conditions or with previous antimicrobial therapy and to an improvement over time in microbiological surveillance with a higher proportion of patients with samples being collected and improved microbiological diagnostic technologies [40,41,43]. Further evaluation of the impact of pneumococcal vaccination on adult CAP is necessary in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Spanish authors have suggested that, besides year-to-year variability, the increase in bacterial and viral isolations over time might reflect a changing epidemiology due to a potential increase in patients with worse socio-sanitary conditions or with previous antimicrobial therapy and to an improvement over time in microbiological surveillance with a higher proportion of patients with samples being collected and improved microbiological diagnostic technologies [40,41,43]. Further evaluation of the impact of pneumococcal vaccination on adult CAP is necessary in our country.…”
Section: Discussionmentioning
confidence: 99%
“…En este apartado abordaremos tres aspectos básicos para la adecuada selección de antibióticos orales en las EAEPOC que son la efectividad, los efectos adversos y el impacto sobre la microbiota, incluyendo la emergencia y selección de resistencias [16,17]. a) Efectividad del antibiótico.…”
Section: Conceptounclassified
“…En el caso de las cefalosporinas intravenosas de 3ª generación, la terapia secuencial más adecuada es cefditoreno por presentar similar espectro y actividad intrínseca [27]. Los beneficios de la estrategia secuencial son directos tanto para el paciente (mayor confort, alta precoz y menor riesgo de infección nosocomial), como para el sistema sanitario (reducción de la estancia hospitalaria y de los costes) [17]. Para cumplir este doble objetivo es preciso asegurar varios puntos: similar espectro bacteriano, buena biodisponibilidad, tolerancia gastrointestinal y baja selección de mutantes resistentes en el tubo digestivo.…”
Section: Antibioticos En La Exacerbacion De La Epocunclassified
“…Recently, the authors of [9] reported that the fluoroquinolones-levofloxacin and moxifloxacin-are the most commonly used antimicrobial agents for the treatment of chronic obstructive pulmonary disease and community-acquired pneumonia. Noteworthy, they not only reveal wide antimicrobial activity, but also possess antiviral action against vaccinia virus, papovavirus, CMV, VZV, HSV-1, HSV-2, HCV, and HIV [10].…”
Section: Introductionmentioning
confidence: 99%